A multi-institute, follow-up, observational study measuring nursing students’ adherence to infection prevention and control protocols in Saudi Arabia - Albarmawi, Marwa; Al Hadid, Lourance; Alnjadat, Rafi; Aljabery, Ahmad (Frontiers in Medicine, 2024)
Background Nursing students learn principles of infection prevention and control (IPC) and hand hygiene (HH) in clinical courses, and their learning is reflected in their practice. Objectives The knowledge, attitude, and practice of principles of IPC and HH of the students were measured prior to and after attending an educational workshop. The adherence of the students to the IPC and HH protocols at the hospital was also observed. Methods This study included a pretest-posttest time series follow-up and an observational part. During the first part of the study, students attended a workshop, which was preceded by a pretest. It was then followed by a posttest directly after finishing the workshop and in 12 weeks. Participants were submitted to an observational part by a trained observer to document certain skills taught earlier during the workshop. Settings Students from three nursing schools in Saudi Arabia participated in the study. Participants A total number of 130 completed the study protocol, and 100 completed the observation part. Results Students were found to experience an improvement in their knowledge, beliefs, and commitment scales after the workshop. The attitude scale remained relatively unchanged over different tests. Most students performed the skills properly and adequately, but some failed to perform certain skills, like hand rub, and the proper use of disinfectants.